Análise do uso de cinza oriunda da queima do lixo urbano utilizada na fabricação de cerâmica branca - Graupmann, Susan Hatschbach (2021)
The urban development of cities promotes a constant increase in the amount of waste that is discarded, causing a negative effect on the environment which leads to irreversible long-term problems. Therefore, it is extremely necessary to make the best use of these residues, whether in their reuse or in their transformation into new materials. Thus, in some cities the gasification system of urban solid waste collected daily is adopted for the production of energy, thus transforming the waste into ash. This material generated by “burning” can be used for the development of materials for civil construction, replacing natural raw materials with waste. The main objective of this study is to use this ash as part of the composition for the manufacture of white ceramics and also to use other residues such as slag, foundry sand and glass powder, for the same production, in order to meet all relevant legislation for your marketing. For the development of the research, samples of 31 different compositions were developed, which underwent tests of resistance to bending, water absorption, linear contraction, density and, for physical and chemical analyses, the XRD and SEM tests. From the raw materials, the tests of FRX, DRX, MEV and EDS were carried out. After these tests, it was observed that most of the samples presented meet the necessary standards for their commercialization, being solid ceramic bricks and porous tiles. The best result using only 15% of natural raw material, 85% of waste, 15% of the composition being ash from the “burning” of urban waste, achieving sufficient resistance for its commercial use.